Active carbon fiber nonwoven fabric, method for manufacturing active carbon fiber nonwoven fabric, element, organic solvent adsorption / desorption treatment device, organic solvent recovery system, organic solvent adsorption / desorption treatment method, and organic solvent recovery method
By adjusting the physical and chemical parameters of activated carbon fiber nonwoven fabrics, the problem of insufficient load durability in the thickness direction is solved, efficient adsorption and desorption performance and long-term shape stability are achieved, and the longevity of activated carbon fiber nonwoven fabrics is promoted and environmentally friendly industrial applications are promoted.
Patent Information
- Application Number
- CN202380061137.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-24
- Publication Date
- 2025-03-21
AI Technical Summary
The load durability of activated carbon fiber nonwoven fabrics in the thickness direction is low, resulting in a reduced winding force and unstable shape in the long-running organic solvent adsorption and desorption treatment device, which affects the adsorption performance.
By adjusting parameters such as BET specific surface area, volume density, graphite crystallinity, R value measured by Raman spectroscopy and half value width of D band, an activated carbon fiber non-woven fabric with excellent adsorption and desorption performance and high load durability were prepared.
The longevity of activated carbon fiber non-woven fabrics is achieved, the long-term stability of the shape stability of the components and the adsorption performance are improved, the generation of industrial waste is reduced, and the environmental burden is reduced.
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to an activated carbon fiber nonwoven fabric, a method for producing the same, and the like. Background Art
[0002] Activated carbon fiber has excellent adsorption and desorption properties for organic solvents, such as large adsorption capacity, fast adsorption speed and fast desorption speed. Activated carbon fiber non-woven fabric is mainly obtained by carbonizing and activating non-woven fabrics composed of precursor fibers such as cellulose, asphalt, etc. such as viscose rayon.
[0003] Due to its excellent adsorption and desorption characteristics, activated carbon fiber can make the organic solvent adsorption and desorption treatment device for adsorbing and desorbing organic solvents contained in the treated gas miniaturized. Therefore, a sheet of activated carbon fiber nonwoven fabric is processed into a cylindrical element and used as an adsorbent for the organic solvent adsorption and desorption treatment device. For example, in Patent Document 1, a wound volume density of 68 kg / m 3 The above-mentioned activated carbon fiber nonwoven fabric is constructed in a cylindrical element for use in a continuous gas adsorption treatment device.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2002-161439 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, compared with general organic fiber nonwoven fabrics, activated carbon fiber nonwoven fabrics have lower load durability in the thickness direction. By repeatedly applying load (or pressure) in the thickness direction, the activated carbon fiber gradually breaks, the shape of the nonwoven fabric is deformed, and as a result, the thickness gradually becomes thinner. This is a phenomenon that occurs when the treated gas is ventilated to the activated carbon fiber nonwoven fabric. By repeatedly supplying and stopping the treated gas, repeating the load state and the no-load state relative to the pressure in the thickness direction, the thickness of the activated carbon fiber nonwoven fabric gradually becomes thinner. As a result, in the case of long-term operation of the organic solvent adsorption and desorption treatment device, the winding force of the element wound into a cylindrical shape of the activated carbon fiber nonwoven fabric is reduced, and the activated carbon fiber nonwoven fabric is deflected downward due to gravity. If the shape stability of the element is impaired, the treated gas will quickly pass through the activated carbon fiber nonwoven fabric, and the adsorption performance of the organic solvent adsorption and desorption treatment device will be reduced.
[0009] In order to ensure the shape stability of the element, measures such as winding it into a cylindrical shape with a stronger tension are considered, but there are problems such as the breakage of the activated carbon fiber nonwoven fabric due to excessive winding tension, which is difficult in industry. In addition, if the thickness of the activated carbon fiber nonwoven fabric becomes thinner over time, the pressure loss of the activated carbon fiber nonwoven fabric increases, and the air volume of the treated gas supplied to the element decreases over time.
[0010] Due to these problems, even if the degradation of the activated carbon fiber nonwoven fabric such as pore clogging has not increased, from the perspective of maintaining the adsorption performance and the air volume stability of the treated gas, the activated carbon fiber nonwoven fabric may be replaced before the shape stability of the element is damaged. However, in recent years, from the perspective of reducing industrial waste, it is desired to extend the life of the activated carbon fiber nonwoven fabric.
[0011] Therefore, the present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide an activated carbon fiber nonwoven fabric having high adsorption and desorption performance for organic solvents and improved load durability in the thickness direction.
[0012] Solutions to Solve Problems
[0013] The present inventors conducted intensive research and found that an activated carbon fiber nonwoven fabric having a specified BET specific surface area, volume density and carbon structure not only has high adsorption and desorption performance, but also can improve load durability in the thickness direction, thereby completing the present invention.
[0014] That is, the present invention is an activated carbon fiber nonwoven fabric, characterized in that:
[0015] BET specific surface area is 1000m 2 / g and above and 2000m 2 / g or less, and the bulk density is greater than 100kg / m 3 , the graphite crystallinity Xg in X-ray diffraction is 0.35 or more, the R value in Raman spectroscopy is 1.20 or more, and the half-value width of the D band in Raman spectroscopy is 145 cm -1 the following.
[0016] For the above-mentioned activated carbon fiber nonwoven fabric of the present invention, it is preferred that the pore volume V with a pore diameter of 0.7 nm or less is 0.7 0.22cm 3 / g or above.
[0017] For the above-mentioned activated carbon fiber nonwoven fabric of the present invention, it is preferred that the pore volume V with a pore diameter of 0.7 nm or less is 0.7 Relative to the total pore volume V a The proportion (V 0.7 / Va ) is 0.30 or more.
[0018] Moreover, the present invention is a method for manufacturing the above-mentioned activated carbon fiber non-woven fabric of the present invention, wherein the manufacturing method includes a step of carbonizing a precursor fiber non-woven fabric to obtain a carbon fiber non-woven fabric, and a step of activating the carbon fiber non-woven fabric, and the activation treatment is performed by a water vapor activation method.
[0019] Furthermore, the present invention is an element constituted by using the above-mentioned activated carbon fiber nonwoven fabric of the present invention.
[0020] Moreover, the present invention is an organic solvent adsorption and desorption treatment device, which has an adsorption tank filled with an adsorption material. The organic solvent adsorption and desorption treatment device adsorbs the organic solvent by bringing the treated gas into contact with the adsorption material and discharges the cleaned gas, and desorbs the adsorbed organic solvent by bringing water vapor or heated gas into contact with the adsorption material and discharges the desorbed gas, wherein the adsorption material includes the above-mentioned activated carbon fiber non-woven fabric of the present invention.
[0021] Moreover, the present invention is an organic solvent recovery system, wherein the organic solvent recovery system includes the above-mentioned organic solvent adsorption and desorption treatment device of the present invention, and an organic solvent recovery device that condenses the desorbed gas discharged from the organic solvent adsorption and desorption treatment device to recover the organic solvent.
[0022] Moreover, the present invention is an organic solvent adsorption and desorption treatment method, which adsorbs the organic solvent and discharges the cleaned gas by bringing the treated gas into contact with the adsorption material, and desorbs the adsorbed organic solvent and discharges the desorbed gas by bringing water vapor or heated gas into contact with the adsorption material, wherein the adsorption material includes the above-mentioned activated carbon fiber non-woven fabric of the present invention.
[0023] Moreover, the present invention is an organic solvent recovery method, which adsorbs the organic solvent and discharges the cleaned gas by bringing the treated gas into contact with an adsorption material, desorbs the adsorbed organic solvent and discharges the desorbed gas by bringing water vapor or heated gas into contact with the adsorption material, and condenses the discharged desorbed gas to recover the organic solvent, wherein the adsorption material includes the above-mentioned activated carbon fiber non-woven fabric of the present invention.
[0024] Effects of the Invention
[0025] The activated carbon fiber nonwoven fabric of the present invention has the above-mentioned specified BET specific surface area, volume density and carbon structure, so it not only has high adsorption and desorption performance, but also can improve the load durability in the thickness direction. Therefore, it is possible to extend the life of the activated carbon fiber nonwoven fabric with excellent adsorption performance, thereby reducing industrial waste and reducing the environmental burden. In addition, the shape stability of the element using the activated carbon fiber nonwoven fabric of the present invention is excellent. In addition, the long-term stability of the adsorption performance of the organic solvent adsorption and desorption treatment device and organic solvent recovery system, and the organic solvent adsorption and desorption treatment method and organic solvent recovery method using the activated carbon fiber nonwoven fabric of the present invention is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram showing one embodiment of the organic solvent recovery system of the present invention. DETAILED DESCRIPTION
[0027] <Activated carbon fiber nonwoven fabric>
[0028] The BET specific surface area of the activated carbon fiber nonwoven fabric of the present invention is 1000 m 2 / g and above and 2000m 2 / g or less. By having the BET specific surface area within the above range, even a small amount of activated carbon fibers can exert sufficient adsorption performance. In addition, the BET specific surface area is more preferably 1100m 2 / g and above 1950m 2 / g or less, more preferably 1200m 2 / g and above 1900m 2 / g or less.
[0029] The volume density of the activated carbon fiber nonwoven fabric of the present invention is greater than 100 kg / m 3 If the bulk density is greater than 100kg / m 3 , even when a load is applied in the thickness direction, the single fiber is not easily broken, so that an element with excellent thickness stability and long-term shape stability can be obtained. In addition, the volume density is more preferably 101kg / m 3 More preferably, 105 kg / m 3 In addition, the upper limit of the bulk density is not particularly limited, but it is difficult to achieve more than 400 kg / m 3 The volume density of .
[0030] The graphite crystallinity Xg of the activated carbon fiber nonwoven fabric of the present invention in X-ray diffraction is 0.35 or more. The graphite crystallinity Xg is obtained by the following formula from the (002) plane peak intensity existing near the diffraction angle 2θ=23-28° of the X-ray diffraction peak curve.
[0031] Xg=Xp÷Xa
[0032] Here, Xp is the difference between the maximum value of the intensity above the tangent line drawn from both ends of the (002) plane peak of the X-ray diffraction peak curve and the tangent line, and Xa refers to the residual intensity obtained by subtracting the air scattering intensity from the (002) plane peak intensity. The air scattering intensity is obtained by scanning in the absence of a sample. Xp is the peak intensity caused by the graphite-like crystal structure, and the graphite-like crystallinity Xg is an indicator of the degree of development of the graphite-like crystal structure. Generally speaking, the larger the value of the graphite-like crystallinity Xg, the greater the graphite-like crystallinity.
[0033] For example, the carbon fiber composed of almost complete graphite crystals has the characteristic of extremely high mechanical strength. The graphite crystallinity Xg of the activated carbon fiber nonwoven fabric of the present invention is more than 0.35, so it has excellent mechanical strength, and even when a load is applied in the thickness direction, the single fiber is not easy to break, so it is possible to obtain an element with excellent thickness stability and excellent long-term shape stability. In addition, the graphite crystallinity Xg is more preferably more than 0.36, and more preferably more than 0.37. In addition, the upper limit of the graphite crystallinity Xg is not particularly limited, but it is difficult to show the BET specific surface area of the present invention under the condition of a graphite crystallinity Xg exceeding 0.85.
[0034] The activated carbon fiber nonwoven fabric of the present invention has an R value of 1.20 or more in Raman spectroscopy. The R value is the relative ratio of the peak intensity (Ig) of the G band to the peak intensity (Id) of the D band in the Raman spectrum, and is calculated by the following formula.
[0035] R value = Id ÷ Ig
[0036] The G band in Raman spectroscopy refers to the wavelength of 1580 cm -1 The peaks observed near the wavelength of 1360 cm -1 The peaks observed nearby originate from the crystal structure of diamond.
[0037] The larger the R value, the greater the intensity of the D band caused by the crystal structure of diamond, which can improve the properties of diamond. Diamond is generally known to have a high hardness. The R value in the Raman spectrometry of the activated carbon fiber nonwoven fabric of the present invention is 1.20 or more, so the mechanical strength is excellent, and even when a load is applied in the thickness direction, the single fiber is not easy to break, so an element with excellent thickness stability and long-term shape stability can be obtained. In addition, the R value is more preferably 1.23 or more, and more preferably 1.25 or more. In addition, the upper limit of the R value is not particularly limited, but it is difficult to show the BET specific surface area of the present invention under the condition of an R value exceeding 3.0.
[0038] The half value width of the D band in the Raman spectroscopic measurement of the activated carbon fiber nonwoven fabric of the present invention is 145 cm -1 The sharpness of the peak of the Raman spectrum is generally related to the crystal state, and it can be said that the narrower the half-value width, the higher the crystallinity. Therefore, the half-value width of the D band becomes an indicator of the crystallinity of the diamond-like crystal structure.
[0039] The half-value width of the D band of the activated carbon fiber nonwoven fabric of the present invention is 145 cm -1 The mechanical strength is excellent, and even when a load is applied in the thickness direction, the single fiber is not easily broken, so an element with excellent thickness stability and long-term shape stability can be obtained. In addition, the half-value width of the D band is more preferably 140 cm -1 In addition, the lower limit of the half-value width of the D band is not particularly limited, but is less than 50 cm -1 It is difficult to express the BET specific surface area of the present invention under the condition of a half-value width of .
[0040] The inventors have found that when the BET specific surface area is 1000-2000m 2 In an activated carbon fiber nonwoven fabric having a weight of 100 g / cm2, by making the bulk density, the graphite-like crystallinity Xg in X-ray diffraction, the R value in Raman spectrometry, and the half-value width of the D band in Raman spectrometry within the above range, the load durability in the thickness direction is significantly improved while maintaining a high adsorption performance for organic solvents. More specifically, it was found that the balance between the graphite-like crystallinity, the diamond-like crystallinity, and the R value is important for the load durability in the thickness direction.
[0041] The activated carbon fiber nonwoven fabric of the present invention preferably has a pore volume V of 0.7 or less. 0.7 0.20cm 3 / g or more. By making the pore volume V 0.7 0.20cm 3 / g or more, so even a smaller amount of activated carbon fiber can exert sufficient adsorption performance. 0.7 More preferably 0.21 cm 3 / g or more, more preferably 0.22cm 3 / g or more. In addition, the pore volume V 0.7 The upper limit of is not particularly limited, but it is difficult to achieve more than 0.50 cm 3 / g pore volume V 0.7 .
[0042] The activated carbon fiber nonwoven fabric of the present invention preferably has a pore volume V of 0.7 nm or less. 0.7 Relative to the total pore volume V a The proportion (V 0.7 / V a ) is 0.28 or more. For the adsorption of organic solvents, sometimes pores with a pore diameter of 0.7nm or less are particularly effective, while pores larger than 0.7nm are not effective for the adsorption of organic solvents. In addition, the presence of mesopores with a pore diameter of 2 to 50nm and macropores with a pore diameter of more than 50nm is also a major reason for the reduction of the mechanical strength of the activated carbon fiber nonwoven fabric. Therefore, by making V 0. 7 / V a When V is 0.28 or more, the pores of the activated carbon fiber nonwoven fabric can effectively function against the adsorption of organic solvents, and the mechanical strength is further improved. As a result, even when a load is applied in the thickness direction, the single fiber is not easily broken, so that an element with excellent thickness stability and long-term shape stability can be obtained. 0.7 / V a It is more preferably 0.29 or more, and even more preferably 0.30 or more. 0.7 / V a There is no particular upper limit on the value, but it is difficult to achieve an activated carbon fiber nonwoven fabric exceeding 0.95.
[0043] <Method for producing activated carbon fiber nonwoven fabric>
[0044] The precursor fiber of the activated carbon fiber nonwoven fabric of the present invention is not particularly limited, and examples thereof include cellulose fibers such as viscose rayon, phenolic resin fibers, polyacrylonitrile fibers, pitch fibers, polyphenylene ether fibers, polyvinyl alcohol fibers, etc. Among them, polyphenylene ether fibers are preferred.
[0045] Specific examples of the polyphenylene ether constituting the polyphenylene ether-based fibers include poly(2,6-dimethyl-1,4-phenylene ether), poly(2,6-diethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), and poly(2,6-dipropyl-1,4-phenylene ether). Among them, poly(2,6-dimethyl-1,4-phenylene ether) is more preferred.
[0046] As the poly(2,6-dimethyl-1,4-phenylene ether), commercially available products may be used as appropriate, and specific examples thereof include PPO640, PPO646, and PPOSA120 manufactured by SABIC Innovative Plastics, and ZYLONS201A and ZYLONS202A manufactured by Asahi Kasei Chemicals Corporation.
[0047] The glass transition temperature of the polyphenylene ether is not particularly limited, but is preferably 170° C. or higher, more preferably 200° C. or higher, and further preferably 210° C. or higher. The upper limit of the glass transition temperature is not particularly limited, but is preferably 230° C. or lower.
[0048] In addition, as the polyphenylene ether used in the present invention, two or more polyphenylene ethers having different glass transition temperatures may be included. Specifically, in addition to the polyphenylene ether having a glass transition temperature of 170°C or more, a polyphenylene ether having a glass transition temperature of less than 170°C may be included. In this case, the content of the polyphenylene ether having a glass transition temperature of 170°C or more is not particularly limited, but is preferably 50% by mass or more, more preferably 65% by mass or more, and further preferably 70% by mass or more relative to the total amount of the polyphenylene ether used. In addition, the upper limit is not particularly limited, but is preferably 100% by mass or less. In the present invention, it is preferred to contain a polyphenylene ether having a higher glass transition temperature (i.e., a high molecular weight) in the range, from the viewpoint of the adsorption and desorption performance of the obtained activated carbon fiber nonwoven fabric and the load durability in the thickness direction.
[0049] In the present invention, after the precursor fiber is made into a nonwoven fabric, it is preferably processed in the order of infusibility treatment, carbonization treatment and activation treatment to obtain an activated carbon fiber nonwoven fabric. In addition, the carbonization treatment and activation treatment may be simultaneously implemented. The method for manufacturing the nonwoven fabric of the precursor fiber is not particularly limited, and the method commonly used in the art can be appropriately adopted. As an example of a preferred formed body of the present invention, a method for manufacturing a nonwoven fabric, for example, spunbonding, meltblowing, spunlace, needle punching, thermal bonding, chemical bonding, etc. can be cited. Among them, needle punching is preferred as a method for manufacturing a short fiber nonwoven fabric.
[0050] In the case where polyphenylene ether fibers are used in the precursor fibers, the infusible treatment can be performed as follows: the nonwoven fabric formed by the polyphenylene ether fibers is subjected to a heat treatment at 120 to 400°C for 0.1 to 100 hours in an air atmosphere with a water vapor concentration of 0.5 to 20 vol.%. Here, the air refers to an environment that has not been specially adjusted. In addition, the water vapor concentration is more preferably 1 to 15 vol.%, and further preferably 2 to 13 vol.%. In addition, the temperature of the infusible treatment is more preferably 140 to 370°C, and further preferably 160 to 350°C. In addition, the time of the infusible treatment is more preferably 1 to 80 hours, and further preferably 2 to 60 hours. In addition, the infusible treatment can also be performed in multiple stages. For example, a two-stage treatment method of treating at 120 to 230°C for 0.1 to 50 hours and then treating at 230 to 350°C for 0.1 to 10 hours can be adopted. The activated carbon fiber nonwoven fabric obtained by carbonizing and activating the non-melting treatment by keeping the water vapor concentration, temperature and time within the above range has excellent mechanical strength, and single fibers are not easily broken even when a load is applied in the thickness direction. Therefore, an element with excellent thickness stability and long-term shape stability can be obtained, which is preferred.
[0051] The activated carbon fiber nonwoven fabric of the present invention can be manufactured by activating (activating) the carbon fiber nonwoven fabric obtained by carbonizing (carbonizing) the precursor fiber nonwoven fabric. The carbonization (carbonizing) can be carried out by a known method, specifically, by heating in the presence of an inert gas. As inert gases, for example, nitrogen and argon can be listed. The heating temperature is generally 800~2500°C, preferably 950~1500°C. The heating time is generally 0.1~40 hours, preferably 0.1~30 hours, more preferably 0.1~10 hours, and further preferably 0.5~5 hours. It should be noted that carbonization and activation can also be carried out simultaneously.
[0052] The activation treatment can be carried out by a known method, specifically, gas activation method and chemical activation method can be listed, but from the viewpoint of fiber strength and thickness stability of nonwoven fabric, water vapor activation method is preferably used. The temperature of water vapor activation is usually 600~1300°C, preferably 800~1000°C, and more preferably 880~1000°C. The time of water vapor activation is usually 0.05~6 hours, preferably 0.1~5 hours, more preferably 0.1~3 hours, further preferably 0.1~1 hours, and particularly preferably 0.1~0.5 hours. The water vapor activation is not particularly limited, for example, preferably carried out in a nitrogen atmosphere with a water vapor concentration of 1~40vol.%, and the water vapor concentration is more preferably 5~30vol.%. In addition, in water vapor activation, it is preferably carried out under an environment with a low oxygen concentration, preferably 5vol.% or less, more preferably 2vol.% or less, and more preferably carried out in an environment without oxygen.
[0053] In the present invention, from the viewpoint of mechanical strength and thickness stability of the activated carbon fiber nonwoven fabric, the carbonization temperature is preferably higher than the activation temperature. More specifically, the carbonization temperature is preferably higher than the activation temperature by 50°C or more, more preferably higher by 60°C or more, and further preferably higher by 70°C or more.
[0054] The activated carbon fiber nonwoven fabric of the present invention is suitable for recovering organic solvents such as ethyl acetate, removing chlorides such as trihalomethane, removing harmful gases such as malodorous gases, NOx and SOx, removing heavy metals such as lead, arsenic and manganese, etc. However, the applications described here are not limited thereto.
[0055] <Components>
[0056] The element of the present invention can be manufactured by winding the activated carbon fiber nonwoven fabric obtained through the above steps into a cylinder. The winding of the activated carbon fiber nonwoven fabric needs to be carried out while adjusting the winding tension so that the activated carbon fiber nonwoven fabric is crushed in the thickness direction without breaking the activated carbon fibers. It is preferred that the packing density A (kg / m 3 ) and the volume density B of activated carbon fiber nonwoven fabric (kg / m 3 ) is 95% or more. It should be noted that the packing density A after the element processing is obtained by the following formula.
[0057] Filling density A = weight of wound activated carbon fiber nonwoven fabric
[0058] ÷(Cylinder height × ((Cylinder outer diameter) 2 - (Inner diameter of cylinder) 2 ) × pi π ÷ 4)
[0059] Here, the cylinder height indicates the height of the activated carbon fiber nonwoven fabric wound into a cylinder, the cylinder outer diameter indicates the outer diameter of the activated carbon fiber nonwoven fabric wound into a cylinder, and the cylinder inner diameter indicates the inner diameter of the activated carbon fiber nonwoven fabric wound into a cylinder.
[0060] <Organic solvent adsorption-desorption treatment device, organic solvent recovery system, organic solvent adsorption-desorption treatment method, and organic solvent recovery method>
[0061] exist Figure 1 An embodiment of the organic solvent recovery system of the present invention is described in detail. The organic solvent recovery system 1 includes an organic solvent adsorption and desorption treatment device 22 having adsorption tanks 2A and 2B. Inside the adsorption tanks 2A and 2B, there is a hollow cylindrical structure in which an activated carbon fiber nonwoven fabric 9 (adsorbent material) is wound in layers on a cylindrical basket-shaped winding core, and an element 8 whose outer peripheral surface is fixed with a metal mesh is detachably provided. Figure 1 In the embodiment, the organic solvent recovery system 1 having two adsorption tanks is exemplified, but the number of adsorption tanks may be one, or three or more. It should be noted that the bottom of the element 8 is closed.
[0062] right Figure 1 The following describes the case where the adsorption tank 2A is in the adsorption process and the adsorption tank 2B is in the desorption process. First, the adsorption process is described. The solvent mixed gas (processed gas) 3 containing the organic solvent passes through the pre-filter 4 and is sent to the adsorption tank 2A by the blower 5 through the lower windshield (Japanese: ダンパー) 6. The organic solvent in the processed gas is adsorbed by the activated carbon fiber nonwoven fabric 9 of the element 8, and is discharged from the exhaust port 12 of the adsorption tank 2A to the outside of the system through the upper windshield 10 as clean air. At this time, the automatic valve 14 of the water vapor supply line 13 is in a closed state.
[0063] Next, the desorption process is described. The water vapor supplied by the water vapor supply line 13 is supplied to the adsorption tank 2B through the automatic valve 15, and the organic solvent in the treated gas adsorbed by the activated carbon fiber non-woven fabric 9 of the element 8 is desorbed and regenerated. The condensate and the uncondensed water vapor containing organic solvent components in the treated gas are sent to the condenser 17 through the desorption gas pipeline 16, and the uncondensed water vapor containing organic solvent components in the treated gas is condensed. The condensate containing a high concentration of organic solvent is sent from the condenser 17 to the separator 19. At this time, the lower windshield 7 and the upper windshield 11 are in a closed state. It should be noted that the gas containing organic solvent components retained in the separator 19 is returned to the treated gas 3 again through the return gas pipeline 20. The organic solvent recovery device in the organic solvent recovery system, for example, includes Figure 1The condenser 17, the cooling water supply line 18 and the separator 19 are shown in the figure, but the present invention is not limited to these.
[0064] For the organic solvent adsorption and desorption treatment device, organic solvent recovery system, organic solvent adsorption and desorption treatment method and organic solvent recovery method of the present invention, in addition to using the activated carbon fiber non-woven fabric of the present invention as the adsorption material, known treatment devices, systems, treatment methods and recovery methods can be used, for example, the treatment devices, systems, treatment methods and recovery methods described in Japanese Patent Gazette No. 6-55254, Japanese Patent Gazette No. 2004-105806 and Japanese Patent Gazette No. 2013-111552 can be used.
[0065] [Example]
[0066] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples. It should be noted that the evaluation methods of physical properties and the like in the following Examples are as follows.
[0067] (Fiber diameter of activated carbon fiber)
[0068] The fiber diameter is obtained by observing a microscope image using a scanning electron microscope (product name: SU1510, manufactured by Hitachi High-Technologies Corporation), reading the fiber diameters of 100 or more fibers from the microscope image, and averaging the read fiber diameters. Note that the fiber diameter means the fiber diameter.
[0069] (BET specific surface area)
[0070] The sample was vacuum dried at 200°C for 16 hours and weighed, and then vacuum dried at 300°C for 1 hour, and then measured using a high-precision gas / vapor adsorption measurement device (product name: BELSORP-MAXII, manufactured by Microtrac BEL). -7 The nitrogen adsorption amount at the boiling point (77K) of liquid nitrogen was measured in the range of ~0.99 to obtain the nitrogen adsorption isotherm of the sample. The nitrogen adsorption isotherm was analyzed by the BET method, which determines the relative pressure range of analysis according to the conditions of adsorption isotherm type I (ISO9277), and the BET specific surface area per unit weight (unit: m 2 / g).
[0071] (Volume density of activated carbon fiber nonwoven fabric)
[0072] According to JIS K1477 7.5 (loss on drying), the weight per unit area (g / m 2 ) is measured. Then, the weight per unit area is divided by the thickness to obtain the bulk density (kg / m3 ). It should be noted that the thickness is calculated by using the area of 4cm 2 The load applied to the sample was adjusted to 1.5 gf / cm 2 To carry out determination.
[0073] (Graphitic crystallinity Xg in X-ray diffraction)
[0074] The sample was ground into powder using an agate mortar and placed in a standard aluminum sample holder manufactured by Rigaku Corporation. The X-ray diffraction peak curve was measured using an X-ray diffractometer (product name: SmartLab, manufactured by Rigaku Corporation) under the following conditions.
[0075] Target: Cu
[0076] Voltage: 40kV
[0077] Current: 30mA
[0078] Cutting conditions for sample measurement: RS1=2 / 3deg, Sollar=5.0deg, S2=0.3mm
[0079] Cutting conditions when measuring without a sample: Sollar = 5.0 degrees, IS = 2 / 3 degrees
[0080] Light receiving part: Ni filter (Dtex / Ultra)
[0081] Scanning range: 2θ=10~40deg
[0082] (R value and half-value width of D band in Raman spectroscopy)
[0083] The Raman spectrum of the fiber surface of the sample was measured under the following conditions using a laser Raman microscope (product name: RAMAN-11, manufactured by Nanophoton Corporation).
[0084] Excitation wavelength: 532nm
[0085] Objective lens: 50 times
[0086] Diffraction grating: 300gr / mm
[0087] Exposure time: 15 seconds
[0088] Cumulative times: 10 times
[0089] For the obtained spectrum, a straight line was taken to 700 cm -1 ~2,000cm -1 After baseline correction in the wave number region, the D band (1360±30cm-1 Nearby), G band (1580±30cm -1 It should be noted that the fitting function uses the Lorentzian function and the Gaussian function as corrections other than the above two peaks. In addition to the two functions, the peak separation analysis is performed in a manner that makes the fitted curve roughly consistent with the measured Raman spectrum. The peak intensity Id of the D band and the peak intensity Ig of the G band are calculated based on the separated peak curve, and the R value (Id / Ig) is calculated. Furthermore, the half-value width (cm2) of the D band is calculated based on the peak curve of the separated D band. -1 ).
[0090] (Pore volume)
[0091] The sample was vacuum dried at 200°C for 16 hours and weighed, and then vacuum dried at 300°C for 1 hour, and then measured using a high-precision gas / vapor adsorption measurement device (product name: BELSORP-MAXII, manufactured by Microtrac BEL). -7 The nitrogen adsorption at the boiling point (77K) of liquid nitrogen was measured in the range of 0.99 to 0.99, and the pore size distribution was obtained by the GCMC method. The model of the GCMC method is Slit, the adsorbent type is Graphitic Carbon, and the fitting method is analyzed by Tikhnov regularization. Based on the obtained pore size distribution, the pore volume V with a pore diameter of 0~0.7nm is calculated. 0.7 and the total pore volume V a Then, the pore volume V is calculated. 0.7 Relative to the total pore volume V a The proportion (V 0.7 / V a ).
[0092] (Load durability in the thickness direction of activated carbon fiber nonwoven fabric)
[0093] After measuring the initial thickness t0 of the sample at a load of 0.15 kPa, a load of 5.0 kPa was applied for 1 minute. Next, after standing for 1 minute without applying a load to the sample, the thickness was measured again at a load of 0.15 kPa. Furthermore, the above operation was repeated 200 times in the order of 5.0 kPa load → standing without applying a load → measuring the thickness at a load of 0.15 kPa, and the thickness t200 of the 200th time was measured. The load durability (%) in the thickness direction was calculated by the following formula.
[0094] Load durability in thickness direction (%) = t 200 ÷t0×100
[0095] Packing density A (kg / m 3 ) and the volume density B of activated carbon fiber nonwoven fabric (kg / m 3 ) is preferably greater than 95%, and the pressure loss of the treated gas supplied to the element by the organic solvent adsorption and desorption treatment device is about 5 kPa. Therefore, from the perspective of long-term shape stability of the element, the load durability of the activated carbon fiber non-woven fabric is preferably greater than 95%.
[0096] (Organic solvent removal performance of components)
[0097] The activated carbon fiber nonwoven fabric was wound around a cylindrical structure with an inner diameter of 100 mm and a length of 575 mm until the mass of the activated carbon fiber reached 5 kg. The packing density A (kg / m 3 ) and the volume density B of activated carbon fiber nonwoven fabric (kg / m 3 The winding tension was adjusted so that the relative ratio (B / A×100) of ) was 95% to obtain a component. Next, the component was mounted on Figure 1 The organic solvent-containing gas treatment device shown in the figure is blown by a blower 5 with a wind volume of 10Nm 3 / minute to the adsorption tank 2A for 18 minutes, the treated gas containing 1000ppm of ethyl acetate at a temperature of 45°C is blown to the activated carbon fiber nonwoven fabric 9, so that the ethyl acetate in the treated gas is adsorbed on the activated carbon fiber nonwoven fabric 9. The ethyl acetate concentration of the treated gas and the gas discharged to the outside of the system is measured at the outlet of the blower 5 and the exhaust port 12 of the adsorption tank 2A using a total hydrocarbon analyzer (product name: HCM-1B, manufactured by Shimadzu Corporation). The opening and closing of the windshield is switched at a time point after 18 minutes after the treated gas is supplied to the adsorption tank 2A, and then the treated gas is supplied to the adsorption tank 2B. On the other hand, water vapor is supplied to the adsorption tank 2A from the water vapor supply line 13 to desorb and regenerate the ethyl acetate adsorbed by the activated carbon fiber nonwoven fabric 9 of the element 8. The adsorption and desorption of ethyl acetate are repeated 10 times, and the removal performance (%) of ethyl acetate is calculated at the time point when the average concentration of ethyl acetate in the gas discharged to the outside of the system is stable. The removal performance (%) of ethyl acetate is calculated by the following formula.
[0098] Ethyl acetate removal performance (%) = average ethyl acetate concentration in the gas discharged to the outside of the system (ppm)
[0099] ÷Average concentration of the treated gas at the outlet of blower 5 (ppm) × 100
[0100] <Example 1>
[0101] The polyphenylene ether fibers obtained by melt spinning poly(2,6-dimethyl-1,4-phenylene ether) (PPO646, manufactured by SABIC Innovative Plas tic) were cut into 51 mm long fibers. 2 The surface and back treatment was carried out under the conditions of 15mm (surface) and 9mm (back) needle depth to obtain a precursor fiber nonwoven fabric. After the obtained precursor fiber nonwoven fabric was heat treated at 190°C for 40 hours in an air atmosphere with a water vapor concentration of 4vol.%, the temperature was further raised to 320°C and heat treated for 2 hours. Next, a carbonization treatment was carried out at 1020°C in nitrogen for 30 hours. Next, an activation treatment was carried out at 950°C for 8 minutes in a nitrogen atmosphere with a water vapor concentration of 25vol.%, to obtain an activated carbon fiber nonwoven fabric with a fiber diameter of 30μm. The evaluation results of the obtained activated carbon fiber nonwoven fabric are shown in Table 1.
[0102] <Example 2>
[0103] An activated carbon fiber nonwoven fabric was obtained in the same manner as in Example 1 except that the activation treatment time was changed to 15 minutes. Table 1 shows the evaluation results of the obtained activated carbon fiber nonwoven fabric.
[0104] <Example 3>
[0105] An activated carbon fiber nonwoven fabric was obtained in the same manner as in Example 1 except that the activation treatment time was changed to 23 minutes. Table 1 shows the evaluation results of the obtained activated carbon fiber nonwoven fabric.
[0106] <Example 4>
[0107] An activated carbon fiber nonwoven fabric was obtained in the same manner as in Example 1 except that the activation treatment was performed at 950° C. for 7 minutes in a nitrogen atmosphere having a water vapor concentration of 25 vol.% and oxygen of 2 vol.%. Table 1 shows the evaluation results of the obtained activated carbon fiber nonwoven fabric.
[0108] <Example 5>
[0109] An activated carbon fiber nonwoven fabric was obtained in the same manner as in Example 2 except that polyphenylene ether fibers obtained by melt spinning poly(2,6-dimethyl-1,4-phenylene oxide) (PPO640, manufactured by SABIC Innovative Plas tic) and poly(2,6-dimethyl-1,4-phenylene oxide) (PPO SA120, manufactured by SABIC Innovative Plas tic) at a mass ratio of 60:30 were used as precursor fibers. Table 1 shows the evaluation results of the obtained activated carbon fiber nonwoven fabric.
[0110] <Comparative Example 1>
[0111] In addition to changing the needle density of the needle loom to 200 needles / cm 2 An activated carbon fiber nonwoven fabric was obtained in the same manner as in Example 2. Table 1 shows the evaluation results of the obtained activated carbon fiber nonwoven fabric.
[0112] <Comparative Example 2>
[0113] An activated carbon fiber nonwoven fabric was obtained in the same manner as in Example 1 except that the carbonization temperature was changed to 850°C and the activation temperature was further changed to 850°C and the time was changed to 70 minutes. Table 1 shows the evaluation results of the obtained activated carbon fiber nonwoven fabric.
[0114] <Comparative Example 3>
[0115] An activated carbon fiber nonwoven fabric was obtained in the same manner as in Example 2 except that the precursor fiber nonwoven fabric was heat treated at 190°C for 40 hours in an air atmosphere with a water vapor concentration of 4 vol.% and then carbonized. Table 1 shows the evaluation results of the obtained activated carbon fiber nonwoven fabric.
[0116] <Comparative Example 4>
[0117] Viscose rayon fibers (manufactured by Daiwabo Rayon Co., Ltd.) with 8 wt.% diammonium phosphate added were cut into 51 mm long fibers. 2 The surface and back treatment was performed under the conditions of 15 mm (surface) and 9 mm (back) needle depth to obtain a precursor fiber nonwoven fabric. The obtained precursor fiber nonwoven fabric was subjected to flame retardant treatment for 1 hour in a nitrogen atmosphere at 400°C. Next, a carbonization treatment was performed in nitrogen at 1020°C for 30 hours. Then, an activation treatment was performed at 950°C for 15 minutes in a nitrogen atmosphere with a water vapor concentration of 25 vol.%, to obtain an activated carbon fiber nonwoven fabric. The evaluation results of the obtained activated carbon fiber nonwoven fabric are shown in Table 1.
[0118] <Comparative Example 5>
[0119] An activated carbon fiber nonwoven fabric was obtained in the same manner as in Example 1 except that the activation treatment time was changed to 3 minutes. Table 1 shows the evaluation results of the obtained activated carbon fiber nonwoven fabric.
[0120] <Comparative Example 6>
[0121] An activated carbon fiber nonwoven fabric was obtained in the same manner as in Example 1 except that the activation treatment time was changed to 31 minutes. Table 1 shows the evaluation results of the obtained activated carbon fiber nonwoven fabric.
[0122]
[0123] According to Table 1, the activated carbon fiber nonwoven fabrics of Examples 1 to 5 all have high ethyl acetate removal performance, and compared with Comparative Examples 1 to 4, the load durability in the thickness direction is excellent, so the long-term shape stability of the element is excellent. In Comparative Example 1, the volume density is small, so the load durability in the thickness direction is low. In Comparative Example 2, the graphite crystallinity Xg in X-ray diffraction is small, so the load durability in the thickness direction is low. In Comparative Example 3, the R value in Raman spectrometry is small, so the load durability in the thickness direction is low. In Comparative Example 4, the half-value width of the D band in Raman spectrometry is large, so the load durability in the thickness direction is low. In Comparative Example 5, the BET specific surface area is small, so the ethyl acetate removal performance is poor. In Comparative Example 6, the BET specific surface area is large, the graphite crystallinity Xg in X-ray diffraction is small, and the R value in Raman spectrometry is small, so the load durability in the thickness direction is low.
[0124] Industrial Applicability
[0125] The activated carbon fiber nonwoven fabric of the present invention can be suitably used as an activated carbon fiber nonwoven fabric having excellent adsorption performance and long-term shape stability, which can replace existing activated carbon fiber nonwoven fabrics, and can greatly contribute to industry.
[0126] Description of Reference Numerals
[0127] 1: Organic solvent recovery system
[0128] 2A: Adsorption tank
[0129] 2B: Adsorption tank
[0130] 3: Solvent mixed gas containing organic solvent (processed gas)
[0131] 4: Pre-filter
[0132] 5: Blower
[0133] 6: Lower windshield
[0134] 7: Lower windshield
[0135] 8: Components
[0136] 9: Activated carbon fiber non-woven fabric
[0137] 10: Upper windshield
[0138] 11: Upper windshield
[0139] 12: Exhaust port
[0140] 13: Steam supply pipeline
[0141] 14: Automatic valve
[0142] 15: Automatic valve
[0143] 16: Desorption gas pipeline
[0144] 17: Condenser
[0145] 18: Cooling water supply pipeline
[0146] 19: Separator
[0147] 20: Return gas line
[0148] 22: Organic solvent adsorption and desorption treatment device.
Claims
1. An activated carbon fiber nonwoven fabric, characterized in that: BET specific surface area is 1000m 2 / g and above and 2000m 2 / g or less, Bulk density greater than 100kg / m 3 , The graphite crystallinity Xg in X-ray diffraction is 0.35 or more, The R value in Raman spectroscopy is 1.20 or more, and The half-value width of the D band in Raman spectroscopy is 145 cm -1 the following.
2. The activated carbon fiber nonwoven fabric according to claim 1, wherein: The pore volume V of pores with a diameter of 0.7 nm or less 0.7 0.22cm 3 / g or above.
3. The activated carbon fiber nonwoven fabric according to claim 1 or 2, wherein: Pore volume V with pore diameter less than 0.7nm 0.7 Relative to the total pore volume V a The proportion (V 0.7 / V a ) is 0.30 or more.
4. A method for producing the activated carbon fiber nonwoven fabric according to claim 1 or 2, wherein: The manufacturing method includes a step of carbonizing a precursor fiber nonwoven fabric to obtain a carbon fiber nonwoven fabric, and a step of activating the carbon fiber nonwoven fabric. The activation treatment is performed by a water vapor activation method.
5. An element formed using the activated carbon fiber nonwoven fabric according to claim 1 or 2.
6. An organic solvent adsorption and desorption treatment device, comprising an adsorption tank filled with an adsorption material, The organic solvent adsorption and desorption treatment device adsorbs the organic solvent by bringing the gas to be treated into contact with the adsorbent material, and discharges the cleaned gas, and desorbs the adsorbed organic solvent by bringing water vapor or heated gas into contact with the adsorbent material, and discharges the desorbed gas. in, The adsorption material comprises the activated carbon fiber nonwoven fabric according to claim 1 or 2.
7. An organic solvent recovery system, wherein: The organic solvent recovery system comprises the organic solvent adsorption and desorption treatment device according to claim 6, and an organic solvent recovery device for recovering the organic solvent by condensing the desorbed gas discharged from the organic solvent adsorption and desorption treatment device.
8. An organic solvent adsorption and desorption treatment method, wherein the treated gas is brought into contact with an adsorbent material to adsorb the organic solvent and discharge the cleaned gas, and water vapor or heated gas is brought into contact with the adsorbent material to desorb the adsorbed organic solvent and discharge the desorbed gas, in, The adsorption material comprises the activated carbon fiber nonwoven fabric according to claim 1 or 2.
9. A method for recovering an organic solvent, comprising: bringing a treated gas into contact with an adsorbent material to adsorb an organic solvent and discharge the cleaned gas; bringing water vapor or heated gas into contact with the adsorbent material to desorb the adsorbed organic solvent and discharge the desorbed gas; and condensing the discharged desorbed gas to recover the organic solvent. in, The adsorption material comprises the activated carbon fiber nonwoven fabric according to claim 1 or 2.
Citation Information
Patent Citations
Cylindrical rotary gas processor
JP1994055254B2
Low-pressure loss and nonwoven fabric-style activated carbon fiber and method for producing the same
JP2002161439A
Equipment for treating organic solvent
JP2004105806A
Adsorption element module, adsorption rotor, adsorption treatment device, and treatment system
CN113975936A
Low-pressure loss and nonwoven fabric-style activated carbon fiber and method for producing the same
JP2002161440A